Penurunan Tekanan Akibat Timbulnya Kerak Pada Pipa Inlet Pompa Sentrifugal di PDAM Rembang - Ahmad Agus Yulianto; santhi wilastari; Fajar Pujiyanto (Politeknik Bumi Akpelni Semarang, 2025)
The centrifugal pump is one of the auxiliary machines at PDAM Rembang, functioning to fill water into the treatment tank/reservoir. There are distribution issues in PDAM Rembang due to interruptions in water distribution to customers, causing customer discomfort. The methods used include data collection, observation, interviews, and literature review. The interview method involved the author questioning the relevant mechanical personnel. Broadly, the author used a qualitative descriptive approach to compile this scientific paper. The results of this research show that the main causes of the pump issues are the lack of pressure in the centrifugal pump due to a blocked inlet valve by mud crusts and leaks in the pipe installation, suction pipe packing, and pump filter. The solution is to equip the pump with filters made of iron or steel coated with stainless steel or brass to prevent corrosion and to block debris and solid substances. A decrease in water flow rate is caused by an increase in pump temperature, blockages in the impeller from soft or solid debris, which leads to impeller imbalance and wear, resulting in the pump not operating optimally. The solution is to replace the damaged impeller and any leaking or corroded pipes. Additionally, there is the issue of wooden branches and metal plates from the river being sucked into the pump, causing impeller wear, resulting in pump instability and pressure drops below the standard 2.0 bar on the pump’s manometer. The solution is for technicians to conduct regular cleaning, inspections, and maintenance every three weeks, ensuring the filter is intact without holes or damage, so debris can be effectively filtered out.